2019
DOI: 10.1007/s10654-019-00579-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of venous thromboembolism: systematic review and meta-analysis of prospective cohort studies

Abstract: The inverse association between physical activity and arterial thrombotic disease is well established. Evidence on the association between physical activity and venous thromboembolism (VTE) is divergent. We conducted a systematic review and meta-analysis of published observational prospective cohort studies evaluating the associations of physical activity with VTE risk. MEDLINE, Embase, Web of Science, and manual search of relevant bibliographies were systematically searched until 26 February 2019. Extracted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 67 publications
3
69
0
Order By: Relevance
“…Given the close link between atherosclerotic CVD and VTE [6], the established relationship between CRF and atherosclerotic CVD, [12] CRF being an objective index of habitual physical activity, and the fact that both disease entities conditions share physical inactivity as a common risk factor [10], these findings may seem unexpected. Though regular physical activity leads to improved CRF, genetic as well as several other environmental factors influence CRF levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the close link between atherosclerotic CVD and VTE [6], the established relationship between CRF and atherosclerotic CVD, [12] CRF being an objective index of habitual physical activity, and the fact that both disease entities conditions share physical inactivity as a common risk factor [10], these findings may seem unexpected. Though regular physical activity leads to improved CRF, genetic as well as several other environmental factors influence CRF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Till recently, evidence on the association between physical activity and the risk of VTE was divergent. In a pooled meta-analysis of 14 prospective cohort studies, we have shown that regular physical activity is associated with reduced risk of VTE [10]. Cardiorespiratory fitness (CRF), as measured by maximal oxygen uptake (VO2max), is the gold standard for assessing aerobic capacity and is an index of habitual physical activity [11].…”
Section: Introductionmentioning
confidence: 99%
“… 9 The increased sedentary lifestyle of the population during the pandemic may be another explanation with regard to the increased incidence of venous thromboembolism during the pandemic. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…The independent and inverse association between CRF, an index for habitual physical activity, and the risk of arterial thrombotic disease (cardiovascular disease, CVD) is very well established. 2,3 Though emerging evidence suggests that regular physical activity is associated with reduced risk of VTE, 4 with the possibility that high CRF levels may reduce the risk of VTE, data on the nature and magnitude of the relationship between CRF and VTE was nonexistent until recently. With the publication of this recent study by Evensen et al, 1 this brings to a total of three studies that have now investigated the association between CRF and VTE risk (Table 1).…”
Section: Does Cardiorespiratory Fitness Really Influence Venous Thrommentioning
confidence: 99%